Japanese: Baltic Sea Region film co-production. Japanese views - Eija Niskanen; Yoshio Kakeo; Silvana Petkovic; Karen Severns (The Research Institute of the Finnish Economy (ETLA), 2010)
Japan is the second-largest movie market in the world, after the United States. For this and other reasons, there is interest from other countries in co-operating with Japanese filmmakers. This report covers the contemporary Japanese film production and distribution scene, detailing the special features and structure of the industry, as well as providing case studies of international film co-production. Special focus lies on the views of Japanese film professionals toward the possibility of film co-productions. The research reveals that the main obstacles to co-production between Japan and the Baltic Sea Region countries (BSR) are the structural differences that exist in film production, as well as Japan's limited knowledge about the BSR and the opportunities the region offers to foreign filmmakers. It suggests that the establishment of long-term support programs for co-production, such as tax incentives for film shooting, and the provision of Japanese-language resources promoting the region would be a positive first step toward drawing greater Japanese interest and enhancing the possibilities for co-production with Japan.
Keywords: 330; Japan; Baltic Sea Region; film/cinema/motion pictures; content industry; international co-production